Corrigendum: Possible Involvement of Hsp90 in the Regulation of Telomere Length and Telomerase Activity During the Leishmania Amazonensis Developmental Cycle and Population Proliferation (Front. Cell Dev. Biol., (2021), 9, 713415, 10.3389/fcell.2021.713415) - Oliveira, Beatriz C. D. de [UNESP]; Shiburah, Mark E. [UNESP]; Paiva, Stephany C. [UNESP]; Vieira, Marina R. [UNESP]; Morea, Edna Gicela O. [UNESP]; Silva, Marcelo Santos da [UNESP]; Alves, Cristiane de Santis [UNESP]; Segatto, Marcela; Gutierrez-Rodrigues, Fernanda; Borges, Júlio C.; Calado, Rodrigo T.; Cano, Maria Isabel N. [UNESP] (Frontiers, 2022)
An author name was incorrectly spelled as Stepany C. Paiva. The correct spelling is Stephany C. Paiva. The authors apologize for this error and state that this does not change the scientific conclusions of the article in any way. The original article has been updated.
Keywords: continuous in vitro passages; Leishmania life forms; LHsp90; telomerase ribonucleoprotein complex; telomeres maintenance